Effect of suckling restriction with nasal flaps on Angus and Criolla calf and dam performance inseminated at fixed time in the arid region of Argentina - Brunello, Gabriela E. (2020)
The effect of suckling restriction with nasal flaps on Angus and Creole calves and dam’s performance fixed time artificially inseminated (FTAI) in an arid zone of Argentina was evaluated. The first experiment was carried out with 146 multiparous cows with calf at foot and 76.2±3.0 days postpartum, assigned to four treatments: Angus cows (n=37) and Creole cows (n=37) with restricted suckling (RS, calves with nasal flaps for 14 days) and Angus (n=35) and Creole (n=37) cows with non-restricted suckling calves (Control, C). On Day 0, the cows received an intravaginal device with progesterone for 8 days and nasal flaps were placed to calves. The FTAI was performed on Day 10 and the pregnancy diagnosis was made at 35 days by ultrasound. In calves, weight was measured on Days 0 and 14 and at weaning (6 months of age). The pregnancy rate was similar between treatments (RS=51.0%; C=53.0%), regardless of breed. At weaning, calves in treatment C were 12.2 kg heavier than calves in RS. The second experiment was performed with 109 multiparous Angus cows with calf at foot with 59.9 ± 0.7 days postpartum, assigned to treatments RS and C. There was no effect on pregnancy rate (RS=66.0%; C=72.0%) and calves from treatment C were 8.6 kg heavier at weaning than those from RS. The results showed that in multiparous cows, the restriction of suckling combined with a hormonal treatment for FTAI does not improve the pregnancy rate and negatively affects the weight of the calves at weaning.